A Monetary Condition Index for Jordan - Al Muhaissen, Tariq; Jiryi, Issa (Jordan Journal of Economic Sciences, 2017)
The MCI is considered as a useful tool for aggregating information related to the combined effect of real interest and exchange rate. The usefulness of the MCI for Jordan can be viewed as a concept that incorporates the effects of the interest and exchange rate channels on aggregate output. Thus, it summarizes the financial conditions in an economy. This paper has constructed an MCI index for Jordan through estimating the effects of real interest and real exchange rates effects on output by using an ARDL model. The results indicate that authorities in Jordan should take the movements of real exchange rate indices into consideration while adjusting monetary and fiscal stances. Also, the results of the model indicated a significant negative impact of real interest rate and real exchange rate on real GDP growth. These results contradict previous studies on transmission mechanism channels in Jordan (Poddar, et al., 2006; Neaime, 2008) and illustrate that the monetary policy in Jordan has some room to maneuver and affect real variables in the long run.